Karakteristik Uji Blaine, Konsistensi Normal dan Waktu Pengikatan Semen yang Menggunakan Tanah Napa Sebagai Bahan Adiktif - Mawardi Anwar; Riri Nofrita; Desy Kurniawati (Departemen Kimia FMIPA UNP, 2012)
It has been investigated about the analysis of characteristic, of cement which used the natural pozzolan in Aripan Solok region in analyzing the blaine, normal consistency and setting time. This research is aimed to recognize the infuencial characteristic of additional natural pozzolan to setting time, blaine and normal consistency. The testing characteristic of natural pozzolan to cement used devices vicat and blaine, the testing pracess was done in some variatation of percentage of 0%, 5% and 9.5 %. The result ot the reseach indicated that the characteristic of addition of natural pozzolan to cement which fulfil SNI 152049-2004 could make the setting time longer in cement hidration and it needed a big volume of water as the normal consistensy. Addition of natural pozzolan in cement will influence the blaine of cement it tells about the maximal addition of natural pozzolan 9.5 %to indicates the blaine of cement to be rough.